2013
DOI: 10.1155/2013/782052
|View full text |Cite
|
Sign up to set email alerts
|

Flow-Volume Parameters in COPD Related to Extended Measurements of Lung Volume, Diffusion, and Resistance

Abstract: Classification of COPD into different GOLD stages is based on forced expiratory volume in 1 s (FEV1) and forced vital capacity (FVC) but has shown to be of limited value. The aim of the study was to relate spirometry values to more advanced measures of lung function in COPD patients compared to healthy smokers. The lung function of 65 COPD patients and 34 healthy smokers was investigated using flow-volume spirometry, body plethysmography, single breath helium dilution with CO-diffusion, and impulse oscillometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 19 publications
(19 reference statements)
4
23
0
1
Order By: Relevance
“…However, the guideline does not make a clear recommendation on which specific technique is the best to use, especially in COPD patients, that lung volumes measured by WBP and MBHD are always not consistent. Consistent with other studies, our study found that TLC%pred, RV%pred and RV/TLC measured in COPD patients by WBP were significantly higher than those measured by MBHD method891119. Coertjens et al found that in 93 COPD patients (29 mild/moderate, 29 severe, 35 very severe), the differences of TLC between the WBP and MBHD method ranged from 30.5% of the predicted value to 38.2% of the predicted value, which is similar to our finding8.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the guideline does not make a clear recommendation on which specific technique is the best to use, especially in COPD patients, that lung volumes measured by WBP and MBHD are always not consistent. Consistent with other studies, our study found that TLC%pred, RV%pred and RV/TLC measured in COPD patients by WBP were significantly higher than those measured by MBHD method891119. Coertjens et al found that in 93 COPD patients (29 mild/moderate, 29 severe, 35 very severe), the differences of TLC between the WBP and MBHD method ranged from 30.5% of the predicted value to 38.2% of the predicted value, which is similar to our finding8.…”
Section: Discussionsupporting
confidence: 92%
“…As previous mentioned, underestimation of lung volume by MBHD is associated with the degree of gas trapping. Our findings align with Jarenback et al 19 in that with single breath or multiple breath helium dilution methods, the helium dilution-derived TLC did not increase based on GOLD classifications. Moreover, O’Donnell et al found FEV 1 %pred <30% is an independent factor for ΔTLC >1L, which also indicates that the difference of lung volumes measured by different methods maybe associated with airflow limitation9.…”
Section: Discussionsupporting
confidence: 92%
“…We have previously shown that baseline impulse oscillometry (IOS) parameters seem to be more affected in moderate-to-severe COPD patients, while volume and diffusion parameters are more affected in severe and very severe COPD patients. In addition, we showed that the lung function parameters are widely spread in Global Initiative for chronic Obstructive Lung Disease (GOLD) stage 2 2. Post hoc investigations of this study identified break points (BPs) in the linear relationship between forced expiratory volume in 1 second (FEV 1 ) percent predicted (%p) and advanced lung function parameters, identifying a change in the lung function pattern when FEV 1 %p drops below 65 3.…”
Section: Introductionmentioning
confidence: 79%
“…Lowering of FEV% measures the degree of airflow obstruction, predominantly in large and intermediate airways, but provides no explanation of the underlying pathophysiology 11. It is therefore generally accepted that FEV 1 by itself cannot describe the complexity of COPD and that FEV 1 alone cannot be used for optimal assessment and management of the disease 7,12…”
Section: Introductionmentioning
confidence: 99%